Plan de manejo de residuos sólidos de la municipalidad distrital de Punchana y su relación con el nivel de satisfacción de los usuarios - 2017 - Díaz Silva, Cecith (2021)
The present work of investigation of the Plan of management of solid residues of the district municipality of Punchana and its relation with the level of satisfaction of the users, 2017, had like objectives: To evaluate the Plan of Management of Residues Solid (PMRS) of the District Municipality of Punchana. ; To evaluate the level of satisfaction of the users of the district of Punchana, regarding the situation of solid waste and Determine the existence of relationship between solid waste management plan and level of user satisfaction, similarly the research hypothesis was :The solid waste management plan of the district municipality of Punchana is directly related to the level of satisfaction of the user, we worked with a sample of 32 officials for the variable solid waste management plan and 138 residents of the Punchana district for the user satisfaction variable; The results obtained show that the solid waste management plan of the District Municipality of Punchana is still insufficient, in terms of the user satisfaction variable, in the indicator Perceived performance reached a regular rating, while the Expectations indicator reached a rating "regular ; Likewise, it was determined that there is a relationship between the existence of a correlation and relationship between the solid waste management plan and the user's satisfaction, thus reaching the research hypothesis.